Strategy of Internationalization by Ukrainian Meat Producers’ Implementation - Tanasiichuk, Alona; Hromova, Olha; Abdullaieva, Anastasiia; Holovchuk, Yulia; Sokoliuk, Kateryna (European Journal of Sustainable Development, 2020)
Scientific and methodical approaches to the definition of international markets for implementation of the strategy of internationalization by Ukrainian meat producers' have been developed, choosing strategy of internationalization by Ukrainian meat producers procedure has been determined, a system of indicators has been developed to assess the marketing appeal of new international markets for Ukrainian meat producers. According to the analysis of practical aspects results of the agrarian enterprise and its associations functioning, a scientific and methodical approach to the integrated assessment of the business environment of international markets attractiveness’ for Ukrainian meat producers by the product group "0207 Poultry Meat" was developed. The proposed approach is based on applying summing up the ranks to rank foreign markets according to the system of dynamic indicators method, which allowed determining the marketing attractiveness of the new international markets for the activity of Ukrainian meat producers in these markets. As a result of the proposed approach application, foreign markets have been identified that demonstrate favorable conditions for doing business with Ukrainian meat producers. It has been proved that the markets of Denmark and Finland have demonstrated favorable conditions for doing business with them, which testifies that internationalization of Ukrainian meat producers’ strategy should be aimed at the formation of future outlines of new markets in the direction which is beneficial to them. Keywords: international business activities, internationalization strategies, attractiveness of international markets marketing, a system of indicators for assessing the marketing attractiveness of new international markets.